2018
DOI: 10.18438/eblip29491
|View full text |Cite
|
Sign up to set email alerts
|

Time to Move EBLIP Forward with an Organizational Lens

Abstract: No abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our research shows that the variation of experience, originally found by Partridge et al (2010), appears to also be valid at an organisational level. The lived experience of USQ Library and the research interviews reinforce the role of the workplace context in building a culture of evidence-based practice (Howlett, 2018a). Library leadership in evidence-based practice is also essential to achieving organisational growth.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our research shows that the variation of experience, originally found by Partridge et al (2010), appears to also be valid at an organisational level. The lived experience of USQ Library and the research interviews reinforce the role of the workplace context in building a culture of evidence-based practice (Howlett, 2018a). Library leadership in evidence-based practice is also essential to achieving organisational growth.…”
Section: Discussionmentioning
confidence: 77%
“…Figure 1 visualises how we describe and conceptualise the Coordinator's position within USQ Library (Howlett, 2018a). It is conceived of and viewed as an enabling role.…”
Section: An Applied Approach To Evidence-based Practice In Academic Lmentioning
confidence: 99%